New Approach for Getting Better Bandwidth in Wireless Mobile Computing (International Journal of Innovative Research in Computer Science & Technology, 2020)
Wireless mobile computing is type of  computation by which various mobile gadgets gives  services to us at numerous ways. In wireless computing  of mobile one can find the working of sensors ad hoc  networks odysseys and rover etc. Not only has this  wireless based mobile computing service also suggested  that a user can take the services of networks any time  anywhere without any disturbances[1]. This includes the  physical location time place authentication etc. which  paves way for making mobile services successful. The  research paper also describes about merits and  disadvantages of wireless mobile computing along with  many challenges faced by it in remote areas.  Additionally, this paper also states how we get adapted to  the ecosystem of wireless network from the long process  of wired networks. Mobile agent is one of the most  important elements in computing. It is clearly described  in this research paper. This research paper also throws  ample amount of light on the working of sensors and its  unique features[12]. Wireless computing makes our life  totally comfortable by its outstanding services. Here all  useful services of that are clearly mentioned. At last the  conducting of wireless mobile computing in all areas of  the world is much more important for the welfare of future generations [9]. This research paper describes  about the steps with measures needed in implementing  wireless computing everywhere.
Keywords: Mobile; Computing; Odessey; Rover; Agent; Sensor